Determination of Normal Ranges of T3, T4, FT4 & TSH in Healthy Individuals of NINMAS by Using Korea and China Kits - Ansari, Israque Hossain; Hasan, Mizanul; Azim, Mohammad Anwar ul; Rashid, Haroun or; Khatun, Sakera; Hossain, Zakir; Mamun, Mustafa (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: The aim of the present study is to determine the own normal range of T3, T4, FT4, & TSH by two kits, one from Korea and another from China in the laboratory of healthy individuals from different divisions of the Institute. Subjects and Methods: Fifty eight (58) adult individuals (39 male &19 female) from different divisions of NINMAS were taken this study. The Korean kit contained coated tube and automated radioimmunoassays (RIA) were performed in case of the Korean kit. Radioimmunoassays with the China kit were done manually by counting in STRATEC-γ Counter of Germany. Immunoassays of T3, T4, and FT4 were done by RIA method. With both the Korean and Chinese kit, TSH assays were performed by IRMA method. Results: The results are analyzed by determining a mean ± 2SD for the normal range. This assumes a Gaussian distribution for the analyte and automatically classifies 5% of the healthy individuals as abnormal. The normal range of T3, T4, FT4 and TSH done by Korean kit were 0.473732561 – 1.8224543301ng/ml (Leaflet normal range, 0.60–2.10ng/ml), 73.61233952– 152.00007428ng/ml (Leaflet normal range, 45.00 – 120.00ng/ml), 7.407195952 – 21.673838528ng/ml (Leaflet normal range, 9.01 – 23.17ng/ml) and 0.077556152 – 5.462788676µIU/ml (Leaflet normal range, 0.30 – 5.00ng/ml) respectively. The normal range of T3, T4, FT4, and TSH done by China kit were 0.922455645 – 1.929268493ng/ml (Leaflet normal range, 0.80 – 2.30ng/ml), 44.87278419 – 141.23445719ng/ml (Leaflet normal range, 42.00 – 135.00ng/ml), 5.80024859 – 32.72492383Pmol/L (Leaflet normal range, 9.50 – 25.50Pmol/L) and 0.807976292 – 5.77167888mIU/L. (Leaflet normal range, 0.30 – 5.00mIU/L) respectively. Conclusion: By estimating few more samples we may use our won estimated normal ranges instead of the leaflet normal ranges. Bangladesh J. Nuclear Med. 18(2): 149-151, July 2015